KAJI EKSPERIMENTAL PENGARUH KONDENSAT UNTUK MENDINGINKAN LIQUID LINE PADA CHEST TYPE MINI COOLER DENGAN METODE RADIANT COOLING - Arda Rahardja Lukitobudi; Wendra Luthfi (KURVATEK, 2020)
Liquid line sub cooler by condensate which is produced from chest type mini cooler wall is one of the methods to increase subcool so that the refrigeration capacity will increase and thus will save energy. Condensate which is produced by chest type mini cooler have lower temperature than the ambient temperature so it will decrease the liquid line temperature, where the condensate is flowed through the tube in tube of 30 cm long with 1 inch diameter to cool the liquid line. Radiant cooling is installed by planted evaporator coils in the cement wall where TXV is used as an expansion device with R22 as the refrigerant and 1 hp compressor capacity. Cabin having dimension of 50cm x 50cm x 50cm is cooled upto 5 0C to chilled 1 kg tomatos. The conclusion is that the chilling time with condensate HX is 35 minutes but without condensate HX is 38 minutes. The mean subcool temperature with condensate HX is 3.32 0C but without condensate HX is 0,03 0C. COPactual with condensate HX is 4.49 but without condensate HX is 4.55. System efficiency with condensate HX is 82.26% but without condensate HX is 80.66%. Energy consumption with condensate HX is 0.635 kWh but without condensate HX is 0.701 kWh. Keywords: radiant cooling, condensate, liquid line sub-cooler.